Targeting metabolic pathways alleviates bortezomib-induced neuropathic pain without compromising anticancer efficacy in a sex-specific manner - Kuppusamy, Panjamurthy; Haque, Md Mamunul; Traub, Richard J.; Melemedjian, Ohannes K. (Frontiers in Pain Research, 2024)
IntroductionChemotherapy-induced peripheral neuropathy (CIPN) is a debilitating side effect of cancer treatment that significantly impacts patients' quality of life. This study investigated the effects of targeting metabolic pathways on bortezomib-induced neuropathic pain and tumor growth using a Lewis lung carcinoma (LLC) mouse model, while exploring potential sex differences.MethodsMale and female C57BL/6J mice were implanted with LLC cells and treated with bortezomib alone or in combination with metformin, dichloroacetate (DCA), or oxamate. Tactile allodynia was assessed using von Frey filaments. Tumor volume and weight were measured to evaluate tumor growth.ResultsMetformin, DCA, and oxamate effectively attenuated bortezomib-induced neuropathic pain without compromising the anticancer efficacy of bortezomib in both male and female mice. The LLC model exhibited a paraneoplastic neuropathy-like phenotype. Significant sex differences were observed, with male mice exhibiting larger tumors compared to females. Oxamate was more effective in alleviating allodynia in males, while metformin and DCA showed greater efficacy in reducing tumor growth in females.DiscussionTargeting metabolic pathways can alleviate CIPN without interfering with bortezomib's anticancer effects. The LLC model may serve as a tool for studying paraneoplastic neuropathy. Sex differences in tumor growth and response to metabolic interventions highlight the importance of considering sex as a biological variable in preclinical and clinical studies investigating cancer biology, CIPN, and potential therapeutic interventions.